Biosynthesis of recombinant interferons in transgenic plants - Holubiev, Pavlo; Kharchenko, Yevgen; Skrotska, Oksana (My University, 2017)
The production of recombinant cytokines with transgenic plants may solve the problem of high demand on drugs against severe diseases, such as hepatitis, AIDS, chronic granulomatous disease, etc. Microorganisms, mammal cell cultures and even plants may be involved in interferon (IFN) production. Considering an array of disadvantages of microbial and mammalian cell cultures, transgenic plants become an object of interest as a perspective producer of interferon.
Keywords: рекомбінантні інтерферони; трансгенні рослини; біосинтез; recombinant interferons; transgenic plants; biosynthesis; кафедра біотехнології і мікробіології